Les routes de l’exil des Vaudois du Piémont vers l’Allemagne (1636-1730) - Albert de Lange (Diasporas: Circulations, Migrations, Histoire)
A fundamental difference exists between the exodus of French huguenots, provoked by the repeal of the Edict of Nantes and that of the Waldensians of Piedmont, in 1687, 1698 and 1730. In these last three cases, it was not a case of illegal flight but of “deportations” organized and documented by the authorities of the Duke of Savoy. We are thus well informed of the road to exile of the Waldensians, all the more so that the minister Jacques Papon published a report on the “deportation” of 1698. This document is published at the end of the article.